Phyto-Immunotherapy, a Complementary Therapeutic Option to Decrease Metastasis and Attack Breast Cancer Stem Cells - Fiorentino, Susana; Urueña, Claudia; Lasso, Paola; Prieto, Karol; Barreto, Alfonso (Frontiers in Oncology, 2020)
In this review, we report on the complexity of breast cancer stem cells as key cells in the emergence of a chemoresistant tumor phenotype, and as a result, the appearance of distant metastasis in breast cancer patients. The search for mechanisms that increase sensitivity to chemotherapy and also allow activation of the tumor-specific immune response is of high priority. As we observed throughout this review, natural products isolated or in standardized extracts, such as P2Et or others, could act synergistically, increasing tumor sensitivity to chemotherapy, recovering the tumor microenvironment, and participating in the induction of a specific immune response. This, in turn, would lead to the destruction of cancer stem cells and the decrease in metastasis. Source of Data: Relevant studies were found using the following keywords or medical subject headings (MeSH) in PubMed, and Google Scholar: “immune response” and “polyphenols” and “natural products” and “BCSC” and “therapy” and “metabolism” and “immunogenic cell death.” The focus was primarily on the most recent scientific publication.